SARS-CoV-2 IGM and IGG rapid serologic test for the diagnosis of COVID-19 in the emergency department. Issue 5 (November 2020) - Cancella de Abreu, Marta; Choquet, Christophe; Petit, Héloise; Bouzid, Donia; Damond, Florence; Marot, Stephane; Ferre, Valentine Marie; Burrel, Sonia; Boutolleau, David; Houdou-Fidouh, Nadhira; Marcelin, Anne-Geneviève; Descamps, Diane; et al.
Highlights: RT-PCR for SARS-CoV-2′s diagnostic has many false negatives and long turnaround times. In our study 20% of RT-PCR negative patients had a rapid Sars-CoV2 IgG/IgM positive. Rapid SARS-CoV2 IgG/IgM may be used as a complementary assay to the RT-PCR. They can be useful in emergency patient's triage and admission. They help avoiding to admit a patient infected with SARS-CoV-2 in a COVID-free area.